10.3928/08910162-20080701-01 (CrossRef Listing of Deleted DOIs, 2000)
Background Suicide is one of the leading causes of death among adolescents in the United States, highlighting the importance of early identification of suicide risk in health care settings. The Ask Suicide-Screening Questions (ASQ) instrument is a validated screening tool designed to identify suicide risk in pediatric populations. Method A quality improvement project was conducted to develop and implement a standardized clinical workflow to support staff in the administration of the ASQ screening tool and improve screening compliance in an outpatient adolescent medicine clinic. The goal of the project was to increase screening compliance to 95% of eligible patients within 8 weeks of implementation. The interventions included implementing a clinical workflow and providing staff education. Discussion Screening compliance improved after implementation of the workflow and staff education, indicating that standardized processes and clear clinical guidance can improve adherence to suicide screening practices. Conclusion These findings support the use of structured workflows and staff training to enhance suicide risk screening in outpatient pediatric settings.